2008
DOI: 10.1210/en.2007-1682
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Thioredoxin-1 Reduces Oxidative Stress in the Placenta of Transgenic Mice and Promotes Fetal Growth via Glucose Metabolism

Abstract: Oxidative stress occurs where there is an imbalance between the production and scavenging of free radicals. Pregnancy per se is a state of oxidative stress due to the increased metabolic activity of placental mitochondria and reduced scavenging ability of antioxidant systems. Overproduction of reactive oxygen species may be associated with impaired fetal growth. However, the physiological influence of antioxidant systems on fetal growth is not well understood. In this study we assessed the effects of antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 48 publications
1
22
0
1
Order By: Relevance
“…It is possible that the concentration of antioxidants used in this study was not optimal or that a combination of various antioxidants is required to see an effect. A previous study has, however, reported that the overexpression of antioxidant thioredoxin increases placental GLUT1 in mice (Umekawa et al 2008). Previous studies from our laboratory have shown that cytokine response to HX/XO may be mediated by the oxidant-responsive transcription factor NF-kB (Coughlan et al 2004).…”
Section: Discussionmentioning
confidence: 72%
“…It is possible that the concentration of antioxidants used in this study was not optimal or that a combination of various antioxidants is required to see an effect. A previous study has, however, reported that the overexpression of antioxidant thioredoxin increases placental GLUT1 in mice (Umekawa et al 2008). Previous studies from our laboratory have shown that cytokine response to HX/XO may be mediated by the oxidant-responsive transcription factor NF-kB (Coughlan et al 2004).…”
Section: Discussionmentioning
confidence: 72%
“…The importance of limiting placental oxidative stress during normal gestation has recently been shown by two studies. First, Umekawa et al (2008) demonstrated that global TXN1 overexpression reduced oxidative damage and enhanced fetal growth in a mouse model. Similarly, we recently reported reduced placental oxidative damage and increased fetal and placental growth with maternal dietary n-3 PUFA supplementation (Jones et al 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…This down- observed gene expression changes in HG conditions. Pregnancy per se can be regarded as a state of oxidative stress due to the increased metabolic activity of placental mitochondria and reduced scavenging activity of antioxidant systems [35]. Thus, diabetic states may enhance the oxidative stress in pregnancy that may accelerate the abnormalities in trophoblast function.…”
Section: Discussionmentioning
confidence: 99%